Impact of COVID-19 pandemic lockdown on post-harvest management of fruits and vegetables in three districts of Andhra Pradesh - G, Sravani; Supriya, Sai; R, Lazima; P, Alisha; M, Srijaya (Journal of Postharvest Technology, 2024)
The spread of COVID-19 pandemic has forced nations to remain in lockdown and stopped all essential activities all over the world. In these circumstances, India is not only plagued by this pandemic, but the emergencies due to COVID-19 have adversely affected the supply chain, and trade of fruits and vegetables. In the present study, impact of COVID-19 pandemic lockdown on postharvest management of fruits and vegetables was studied using a quantitative research design. A sample size of 120 fruit and vegetable farmers were selected from Andhra Pradesh, India. The information was collected through telephonic interviews with the aid of a semi structured questionnaire. The collected data was statistically analyzed using descriptive statistics and Chi- square (χ2) testing of hypotheses was used to find out the association between variables. Findings showed that there was a significant statistical association (p<0.05) between the farming experience, type of pre-treatments selected and maturity indices adopted for the produce. Type of packaging material and incurred transportation losses to produce were also found to be significantly associated. Results disclosed that most of the farmers lack formal knowledge of on- farm practices, despite their farming experience and hence resulted in post-harvest losses. There was no significant association found between farming experience and postharvest losses. The major postharvest losses occurred at the transportation and marketing phase of the supply chain irrespective of the lock down situation.